Bacterial Transposons containing Markers for Fungal Gene Disruption - L. Hamer; S. Gilger (Fungal Genetics Reports, 1997)
We have constructed 2 tn5-containing plasmids, pLH1 and pLH3, specialized towards mutagenesis of genes from fungi which are auxotrophic for arginine or sensitive to hygromycin (such as the filamentous fungi Aspergillus nidulans and Magnaporthe grisea.) These plasmids are also a useful means of integrating additional marker genes in the plasmid backbone.